Protection of Life and Health of Citizens in The Sphere of Production and Circulation of Medicines and Medical Products: A Legal Aspect - Fedotova, Hanna; Kosilova, Olga; Maryna Kobets, Maryna Kobets (Journal of History Culture and Art Research, 2020)
The statistics, listed in the article, prove that the most frequent encroachment on the life and health of citizens in the field of production and circulation of medicines and medical products is the falsification of medicines that is in demand every day and advertised on television and radio; including painkillers, antibiotics, psychotropic substances. There are a number of factors contributing to the commission of offenses in the sphere of production (manufacturing), storage, sales (realizations), import of medicines. The sphere of public procurement of medicines remains the most corrupted area of public relations. Thus, the most widespread type of crime in the health sector is theft of budget funds by excessive prices on market prices, when organizing the purchase of medicines, products and medical equipment for health care institutions. The most widespread corruption schemes for public procurement of medicines in Ukraine are the so-called «cartel conspiracies», in other words, behind-the-scenes agreements between companies on the distribution of winning bidding and excess pricing of medicines in the State Register of wholesale and retail prices. All considered violations require the development of a clear regulatory mechanism at the legislative and regulatory levels of the processes of production, control and marketing of medicinal products; only such actions will contribute to counteracting fraud and illicit circulation of falsified medicines and will provide protection of life and health of citizens.